KARTAGENER SYNDROME: A CASE REPORT - Najafi, Samane; Mohammadpour, Ali; Eshghizadeh, Maryam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Kartagener syndrome is a rare genetic disorder which includes a triad of bronchiectasis, chronic sinusitis, and situs inversus. Primary ciliary dyskinesia (PCD) can be one of the causes of the above symptoms in this syndrome. This study aims to contribute toward a greater understanding of Kartagener syndrome by reporting a rare case. This 16-year-old boy was hospitalized in the internal ward of 22 Bahman Hospital in Gonabad on February 23, 2016 and presented with suspected Kartagener syndrome and PCD, whose diagnosis of Kartagener syndrome and PCD was confirmed according to biopsy of the nose and antitrypsin test. The patient also underwent electrocardiography, chest X-ray, pelvic and abdominal ultrasound, and computed tomography scan with high resolution and no contrast of the chest, abdomen, and sinuses. As a rare disorder, Kartagener syndrome should be borne in mind in differential diagnoses of chronic respiratory infections and must be diagnosed as early as possible to improve patient's quality of life.